Climate shocks, livestock assets, and consumption dynamics: Evidence from rural Ethiopia - Elias, Hailu; Alemu, Tekie (International Food Policy Research Institute, 2014)
This policy note summarizes research that analyzed the adverse impact of climate-related shocks on farm households’ real per capita consumption and asset ownership over time, as well as factors that exacerbate or ameliorate those adverse impacts.